Interactions between plant pathogens and their implications for crop protection - Tanaka, Ayano (SLU/Dept. of Forest Mycology and Plant Pathology, 2021)
One plant may often be infected by more than one pathogen species. It is assumed that species which exploit the same resource have the potential to affect each other. Plant diseases where more than one pathogen is involved in the development of infection are usually termed as ¨disease complex¨. Different pathogen species causing similar symptoms on a single host plant species may complicate diagnosis and subsequent control, and besides, the complex interaction may alter the expression of host disease severity. However, the knowledge of multiple-pathogen interactions is still limited, and therefore recent epidemiologic studies have begun to focus on this subject. Pathogen-pathogen interaction varies due to different interaction mechanisms. For example, antagonism where one pathogen has a negative effect on the development of the other. Antagonistic interaction can often be divided into three different mechanisms. First, pathogens produce antimicrobial components, and therefore the development of the other pathogen is supressed. Second, pathogens induce systemic resistance by activating the defence mechanism in the plant-host. Finally, pathogens which out-compete the other pathogens because they are quicker in consuming nutrients and occupying the ecological niches. Another example of multiple-pathogen interactions is synergism, where one pathogen promotes the development of another, and thus it may result in more severe disease symptoms. The objective of this study was to learn about pathogen-pathogen interactions in plant diseases via literature review and test a method for analysing the interactions in vitro, using plant pathogens from the Fusarium genus (F. graminearum, F. culmorum & F. oxysporum). The lab result showed that F. oxysporum, in the interaction setup, was quicker in consuming nutrients and occupied most of space on PDA at temperature 25°C, whereas F. culmorum seemed to be supressed. Hence, F. oxysporum seemed like a better competitor toward F. culmorum under the in vitro conditions tested. Compared to the traditional studies where focus is on only one pathogen, the study of multiple-pathogen interactions has just begun recently, and it is important to establish the experimental methods to understand disease complexes, the synergisms and antagonism in pathogen-pathogen interactions, leading to identification of pathogens in relation to the crop production system. This will require a holistic understanding of how a host responds to co-infection and how pathogens interact and coexist; therefore, this needs to involve the interdisciplinary research collaboration between bacteriologists, mycologists and virologists.